Diet and Feeding Habits of Tor tambroides (Bleeker, 1854) in Wa River, Nan Province - คีรีแลง, จุลทรรศน์; ล้อทองคำ, อมรชัย; ใจสุข, เชาวลีย์ (Recent Science and Technology, 2019)
The study of gut content analysis of Tor tambroides (Bleeker, 1854) in Wa River, Nan Province was conducted by monthly sampling from a 12 month period (March 2015 to February 2016) The objective of the study was to examine the stomach content and the ratio of digestive tract to body length. From a total number of 136 specimens, the total length of fish ranged from 8.5 - 92.0 cm. Total length was 30.08 ± 15.93 cm. The intestine length of fish ranged from 5 - 205 cm. and the average intestine length was 44.85 ± 37.68 cm. Results obtained from the type and food component found in stomach content of T.tambroides consisted of plants 44.93%, followed by algae 8.53%, shellfish, 17.95%, insects 8.05%, aquatic insect larva 5.80%, organic matter detritus 5.15%, fish 5.31% and others 4.27%. Algae were dominant food items in young fish, while parts of shellfish were dominant food items in adult. Insects were observed in all sizes of fish. Fish were dominant food items in big fish. The ratio of intestine length to body length was 1: 1.36 ± 0.50. The equation of total length and intestine was Li = 0.4081TL1.345, r = 0.8924. The correlation coefficient showed that the intestine length of fish varied with the total length. From the result of their feeding habits, T. tambroides can be classified as omivorous.